Efeito de forças hidrodinâmicas em colisões partícula-superfície em diferentes meios fluidos - Melo, Karla Raphaela Braga de (Universidade Federal de São Carlos, 2023)
Energy dissipation in systems, such as solid-gas and solid-liquid, can occur in several ways, including resistance to motion, interfacial interactions, deformation, and particle collision. In gas-solid flows, the main energy dissipation occurs due to plastic deformation, internal friction or elastic losses during interactions between particles or between particles and surfaces. On the other hand, in liquid flows, factors such as surface tension, adhesion and dissipative forces are relevant. One of the ways to measure this dissipation is by measuring the restitution coefficient, a dimensionless coefficient given by the ratio between the restitution and impact velocities. In liquids, this parameter is also related to the liquid's ability to dissipate energy during a collision and is called the effective coefficient of restitution. The study of this dissipation is crucial to understanding system behavior, optimizing processes, and designing efficient devices. In this context, this work aims to investigate the various factors involved in collisions that affect the restitution coefficients and the effective restitution coefficient. To this end, commercial particles of ABS, porcelain, carbon steel (coated or not with a polymeric film), polypropylene and high alumina were characterized in terms of density, diameter and Young's modulus and used in experimental particle-surface collision tests. In tests in air, the results showed a decreasing trend in the coefficient of restitution with the increase in the number of successive impacts in collisions and the ratio of particle diameter/thickness of the collision plate. Furthermore, the influence of material properties on the restitution coefficient values was observed, including the effect of a polymeric film covering carbon steel spheres. In liquid experiments, effective restitution coefficient results were obtained at different concentrations of glycerin solution, and a directly proportional relationship was observed between the increase in this parameter and the Stokes number. Finally, experimental data from the literature were used to validate a proposed correlation for predicting the dry restitution coefficient as a function of particle properties, wall thickness and impact velocity. The results demonstrated that the correlation satisfactorily described the experimental data and proved to be an effective tool in predicting this parameter.
Effect of hydrodynamic forces on particle-surface collisions in different fluids
Keywords: Colisões; Coeficiente de restituição; Coeficiente de restituição efetivo; Número de Stokes; Correlação; Collisions; Coefficient of restitution; Effective coefficient of restitution; Stokes number; Correlation; ENGENHARIAS::ENGENHARIA QUIMICA